Polycystins recruit cargo to distinct ciliary extracellular vesicle subtypes in C. elegans - Inna A. Nikonorova; Elizabeth desRanleau; Katherine C. Jacobs; Josh Saul; Jonathon D. Walsh; Juan Wang; Maureen M. Barr (Nature Communications)
Abstract Therapeutic use of tiny extracellular vesicles (EVs) requires understanding cargo loading mechanisms. Here, we use a modular proximity labeling approach to identify the cargo of ciliary EVs associated with the transient receptor potential channel polycystin-2 PKD-2 of C. elegans. Polycystins are conserved ciliary proteins and cargo of EVs; dysfunction causes polycystic kidney disease in humans and mating deficits in C. elegans. We discover that polycystins localize with specific cargo on ciliary EVs: polycystin-associated channel-like protein PACL-1, dorsal and ventral polycystin-associated membrane C-type lectins PAMLs, and conserved tumor necrosis factor receptor-associated factor (TRAF) TRF-1 and TRF-2. Loading of these components to EVs relies on polycystin-1 LOV-1. Our modular EV-TurboID approach can be applied in both cell- and tissue-specific manners to define the composition of distinct EV subtypes, addressing a major challenge of the EV field.